Utilization of the Aspergillus nidulans pyrG gene as a selectable marker for transformation and electroporation of Neurospora crassa - G. E. Turner; T. J. Jimenez; S. K. Chae; R. A. Baasiri; K. A. Borkovich (Fungal Genetics Reports, 1997)
We report the complementation of the Neurospora crassa pyr-4 mutation with the Aspergillus nidulans pyrG gene. The use of the pyrG gene as a selectable marker for N. crassa transformation offers several advantages: a non toxic nutritional selection, the ability to put single-copy transformants through a sexual cross without the occurrence of RIP (Repeat-Induced Point mutation) by alleles of the pyr-4 gene, and a relatively-high electroporation efficiency. These traits were exploited for targeted gene replacement in N. crassa. In addition, the high electroporation efficiency of pyrG achieved using supercoiled circular DNA renders it an ideal marker for random insertional mutagenesis studies in N. crassa.